2013
DOI: 10.1038/nphys2766
|View full text |Cite
|
Sign up to set email alerts
|

Spintronic magnetic anisotropy

Abstract: An attractive feature of magnetic adatoms and molecules for nanoscale applications is their superparamagnetism, the preferred alignment of their spin along an easy axis preventing undesired spin reversal. The underlying magnetic anisotropy barrier -a quadrupolar energy splitting -is internally generated by spin-orbit interaction and can nowadays be probed by electronic transport. Here we predict that in a much broader class of quantum-dot systems with spin larger than one-half, superparamagnetism may arise wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
120
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(129 citation statements)
references
References 82 publications
9
120
0
Order By: Relevance
“…(C.5)] are not important, because this approach preserves positivity. At the same time we note that the principal parts are required to catch important physics such as renormalization of energy levels in some systems [66,67,68,69]. By simulating different systems we also observed that with neglected principal parts the 1vN and the Redfield approaches give the same results.…”
Section: Appendix G Which Approach To Use?supporting
confidence: 65%
“…(C.5)] are not important, because this approach preserves positivity. At the same time we note that the principal parts are required to catch important physics such as renormalization of energy levels in some systems [66,67,68,69]. By simulating different systems we also observed that with neglected principal parts the 1vN and the Redfield approaches give the same results.…”
Section: Appendix G Which Approach To Use?supporting
confidence: 65%
“…28 here becomes vanishingly small. Therefore the effective electron mediated spin-spin interactions dominates the properties and control of the molecular dimer.…”
Section: (C)mentioning
confidence: 83%
“…Arrays of magnetic molecules inserted between conducting leads, moreover, provide an important forum to investigate fundamental magnetic properties of finite one-dimensional Ising or Heisenberg chains [14][15][16] as well as potential for electrical and thermal control of the magnetic state. Certain classes of molecules, e.g., metal-phthalocyanines (MPc) and metal-porhyrins (MP) present chemical stability with specific optical and electrical properties make them highly appreciated for technological applications including organic field effect transistors [17,18], light emitting devices [19,20] and photovoltaic cells [21], and for fundamental studies [7,[22][23][24][25][26][27].While incorporation of magnetic elements in molecular compounds can have a significant effect on the overall molecular transport properties [7], the main established route to spintronics manipulations entails external magnetic fields [2] or ferromagnetic electrodes [28,29], often exploiting spin transfer torques from spin-polarized scattering [30] or Coulomb interaction [31]. Here, we propose a different route to molecular spintronics based on voltage induced control of magnetic interactions that allows for all electrical control of the transport properties.…”
mentioning
confidence: 99%
“…[1,2] The synthesis of graphene and its different analogues,t he main-groupbased planar 2D materials, has therefore attracted significant attentiono wing to their unique and tunable electronic, optoelectronic, and spin-electronic properties. [3][4][5][6][7][8][9][10][11][12][13] Furthermore, main-group-based systemss how long spin relaxationt imes owing to weak spin-orbit coupling.…”
Section: Introductionmentioning
confidence: 99%